INTENSITY OF USE OF RICE PRODUCTION TECHNOLOGY: LESSON FROM AGRICULTURAL TRANSFORMATION AGENDA PARTICIPANTS IN NORTH WEST, NIGERIA - Balogun, O. S.; Damisa, M. A. (FUDMA JOURNAL OF SCIENCES, 2023)
The study examined the Intensity of use of improved technology among rice farming households of Agricultural Transformation Agenda (ATA) in North-Western zone of Nigeria. 571 respondents were selected using a multi-stage sampling technique. Data were collected through structured questionnaires on socio-economic variables such as respondent’s age, marital status, gender, household size and level of education. Descriptive statistics was used to describe the socio-economic variable. Cragg’s model (Double hurdle) was used to examine the influence of some socio-economic and institutional variables on participation and intensity of use by the respondents. The study revealed that farm size and communication assets (radio/Television sets and phones) significantly influenced the farmer’s decision to participate (P>0.01). Gender of household head, ownership of livestock (Oxen) and extension agent contacts influenced respondent’s decision to participate (P<0.05), market distance had significant influence on participation decision (P<0.01). Also, intensity of use of package of practices was influenced significantly by farm size and households’ size (P<0.01) while communication assets ownership significantly influenced package of practices use (P<0.05), respectively. There were complains of fluctuations of input/output prices insect pests and inadequate extension visits the study recommended that farmers’ information and sensitization system should be considerably improved. Furthermore, attention should be given to well organized extension visits and formidable marketing system in agricultural projects for effective input output delivery.